Association between smartphone overdependency and mental health in Korean adolescents during the COVID pandemic; Age-and gender-matched study - Kim, Na-Hye; Lee, Jae-Moo; Yang, Seo-Hyung; Lee, Jung-Min (Frontiers in Public Health, 2022)
Purpose This study aimed to examine the relationship between smartphone dependency (SD) and mental health (MH) in adolescents in order to develop and implement plans pertaining to SD control. Methods Raw data from the 16th Online Adolescent Health Behavior Survey in 2020 were analyzed. A total of 482 respondents were selected as study subjects based on their experience of smartphone overdependence (SO), specifically, 241 participants whose score for SO was 37 or higher (Group 2) and age- and gender-matched 241 participants whose score was lower than 10 (Group 1). Results Frequency analysis, cross-tab analysis (χ2 test), and multinomial logistic regression were performed Analysis shows that the MH affecting the increase in SO is the subjective perception of happiness, subjective perception of stress, sadness and despair, and experience of Loneliness. But, the variable affecting the reduction is the subjective evaluation of sleep quality. The likelihood of SO increased as adolescents felt unhappier [Exp (β) = 2.408] and more stressed [Exp (β) = 4.453] and more often felt lonely [Exp (β) = 8.149], but the likelihood decreased as they had neither sufficient nor insufficient sleep duration [Exp (β) = 0.344]. The findings suggest that it is necessary to develop aggressive measures for the prevention and management of MH in adolescents showing SO because mental health is closely linked to SD. In developing the measures, realistic approaches to widely pervasive SO among adolescents should be explored by taking into account MH factors, that is, predictors of SO, and the characteristics of youths, such that they can self-control smartphone use and form desirable life habits.